Handbook on the rule of law - Rule. (Cheltenham, UK Northampton, MA Edward Elgar Publishing, 2018)
"In the last half century, the rule of law has increasingly been appealed to as a common global value. The Handbook on the Rule of Law analyses the appeal of this idea, its context and background through a range of questions about the character, history and global reach of the rule of law, offering readers a definitive understanding of this central global norm. Original contributions from leading academics explore the rule of law conceptually and historically through its associated institutions, as well as examining detailed cases evaluating how the everyday application of the rule of law impacts society as a whole. Exploring a wide range of research on the social, political and economic dimensions of the rule of law, this Handbook clearly illustrates the link between the rule of law and the global political system. This informative Handbook will be key reading for postgraduate students of international relations, global politics and law, as well as for legal scholars wanting to build upon their knowledge with a wider account of the rule of law. Rese
The advantages of a thin view / |r Jørgen Møller -- |t The promise of a thick view / |r Adriaan Bedner -- |t Difficulties with measuring the rule of law / |r Tom Ginsburg -- |t The rule of law, legal pluralism, and challenges to a Western-centric view : some very preliminary observations / |r Peer Zumbansen -- |t Arbitrary power and the ideal of the rule of law / |r Martin Krygier |g with |r Adam Winchester -- |t The centrality of predictability to the rule of law / |r Christopher May -- |t The rule of law in inter-national relations : contestation despite diffusion : diffusion through contestation / |r Antje Wiener -- |t The rule of law : an outline of its historical foundations / |r Pietro Costa -- |t Minimising Magna Carta and modernising exposition of the rule of law in the English historical constitution / |r J.W.F. Allison -- |t Turning the rule of law into an English constitutional idea / |r J.W.F. Allison -- |t The rule of law and the rise of capitalism / |r Tor Krever -- |t The rule of law and its application to the United Nations / |r Clemens A. Feinäugle -- |t Power rules : the World Bank, rule of law reform, and the World Development Report 2017 / |r Deval Desai -- |t The rule of law and the European Union / |r Amichai Magen, |r Laurent Pech -- |t Non-governmental organisations and the rule of law : the experience of Latin America / |r Fiona Macaulay -- |t Lawyers and the rule of law / |r David Howarth -- |t The rule of law and legal education : do they still connect? / |r John Flood -- |t The rule of law, new constitutionalism, and transnational legality / |r A. Claire Cutler -- |t Global administrative law / |r Valentina Vadi -- |t The rule of law and feminism : the dilemma of differences / |r Anna Loretoni -- |t The rule of law and Islam / |r Jerg Gutmann, |r Stefan Voigt -- |t The rule of law and human rights / |r Mona Rishmawi -- The rule of law from a law and economics perspective / |r Mariana Mota Prado -- |t The rule of law, institutions, and economic development / |r Lydia Brashear Tiede -- |t The legal empowerment of the poor / |r Dan Banik -- |t The rule of law as a marketing tool : the International Criminal Court and the branding of global justice / |r Christine Schwöbel-Patel -- |t The rule of law and terrorism / |r Clive Walker -- |t Post-conflict peacebuilding and the rule of law / |r Teresa Almeida Cravo -- |t Rule of law in Asia : the case of China / |r Thomas E.
Includes bibliographical references and indexes.